2019
DOI: 10.3390/ijms20010225
|View full text |Cite
|
Sign up to set email alerts
|

Methylseleninic Acid Induces Lipid Peroxidation and Radiation Sensitivity in Head and Neck Cancer Cells

Abstract: Combination radiation and chemotherapy are commonly used to treat locoregionally advanced head and neck squamous cell carcinoma (HNSCC). Aggressive dosing of these therapies is significantly hampered by side effects due to normal tissue toxicity. Selenium represents an adjuvant that selectively sensitizes cancer cells to these treatments modalities, potentially by inducing lipid peroxidation (LPO). This study investigated whether one such selenium compound, methylseleninic acid (MSA), induces LPO and radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…We found that BAP31 deficiency upregulated LPS-induced superoxide and hydrogen peroxide production. Superoxide may be protonated to form hydroperoxyl radical or dismutated to form hydrogen peroxide, both of which may contribute to the initiation of lipid peroxidation [43][44][45]. Consistent with previous results, BAP31 deficiency exacerbated superoxide anion production following LPS treatment, resulting in lipid damage in microglia.…”
supporting
confidence: 89%
“…We found that BAP31 deficiency upregulated LPS-induced superoxide and hydrogen peroxide production. Superoxide may be protonated to form hydroperoxyl radical or dismutated to form hydrogen peroxide, both of which may contribute to the initiation of lipid peroxidation [43][44][45]. Consistent with previous results, BAP31 deficiency exacerbated superoxide anion production following LPS treatment, resulting in lipid damage in microglia.…”
supporting
confidence: 89%
“…In addition to methylselenocysteine, methylseleninic acid has been reported as a direct precursor of methylselenol, the key metabolite responsible for selenium’s anti-cancer activity (El-Bayoumy and Sinha 2004 ), and effective against prostate cancer (Zhao et al 2004 ). By inducing lipid peroxidation, methylseleninic acid sensitizes head–neck squamous cell carcinoma to radiation (Lafin et al 2019 ).…”
Section: Pharmacology Of Organoselenium Compoundsmentioning
confidence: 99%
“…Among the well-known mechanisms and regulatory pathways of the antitumor activity of MCA, the following can be distinguished: glutathione-dependent induction of lipid peroxidation [34], the inhibition PI3K/AKT/mTOR pathway and activation of FOXO proteins [54], the inhibition of the activity of deacetylases and DNA-methyltransferases [114], the activation of the Keap1/Nrf2 pathway via upregulation of miR-200a [32], the activation signaling pathways of adaptive and pro-apoptotic UPR, the down-and up-regulation of the ER-resident selenoprotein genes expression [3], the inhibitions of angiogenesis by suppressing β3-integrin and interrupting its clustering [41] and other cytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that human hepatoma HepG2 cells with a high concentration of glutathione are more sensitive to MSA [33]. In addition, it was found that MSA makes cancer cells more sensitive to radiation and causes their toxicity through glutathionedependent induction of lipid peroxidation, which was demonstrated by the example of head and neck squamous carcinoma cell lines [34]. Possibly, the selective cytotoxicity of MSA against cancer cells can be explained by the higher lipid content in cancer cells compared to normal cells [35][36][37][38][39].…”
Section: Reasons and Molecular Mechanisms Of The Cytotoxic Effect Of Msa On Cancer Cellsmentioning
confidence: 96%